2017
DOI: 10.1016/j.drugalcdep.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality/religiosity, substance use, and HIV testing among young black men who have sex with men

Abstract: Background Spirituality and religiosity may serve as both a resource and a barrier to HIV prevention with young black men who have sex with men (YBMSM). We examined indices of spirituality/religiosity as correlates of binge drinking, stimulant use, and recent HIV testing in a sample of YBMSM. Methods From 2011–2013, annual venue-based surveys of sexually active YBMSM ages 18–29 were conducted in Dallas and Houston, Texas. Binge drinking and stimulant use were assessed in the past two months. Participants rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…However, higher levels of religion and spirituality at the baseline were related to increased marijuana use at the 6-month follow-up, as participants reported that they felt more spiritually connected when they were high on marijuana. Another recent mixed-results study of 1565 young black homosexual men in Houston and Dallas showed that participation in spiritual and religious activities is an important source of resilience, albeit a risk for these men (Carrico et al 2017). On the one hand, the odds of substance use diminished when the men had higher levels of “spiritual coping” (i.e., the ability to tap into spiritual support and look for meaning in a traumatic situation).…”
Section: Sections Of the Studymentioning
confidence: 99%
“…However, higher levels of religion and spirituality at the baseline were related to increased marijuana use at the 6-month follow-up, as participants reported that they felt more spiritually connected when they were high on marijuana. Another recent mixed-results study of 1565 young black homosexual men in Houston and Dallas showed that participation in spiritual and religious activities is an important source of resilience, albeit a risk for these men (Carrico et al 2017). On the one hand, the odds of substance use diminished when the men had higher levels of “spiritual coping” (i.e., the ability to tap into spiritual support and look for meaning in a traumatic situation).…”
Section: Sections Of the Studymentioning
confidence: 99%
“…Younger MSM (<30 years old) are moderately more likely to never have been tested for HIV [ 19 , 20 ], and common barriers to HIV testing, such as not having insurance or transportation to a testing place, are reported more by younger MSM [ 21 , 22 ]. Substance use is also associated with decreased odds of recent HIV testing and increased likelihood of unknown HIV infection [ 23 , 24 ], suggesting an unmet need for HIV testing promotion, particularly among younger MSM and those who use substances.…”
Section: Introductionmentioning
confidence: 99%
“…Another study cited that religious behavior among gay men is associated with higher CD4 counts (Woods et al 1999). Some research indicates that engagement in R/S activities among Black MSM is associated with greater odds of HIV testing (Carrico et al 2017). However, certain HIV risk factors such as substance use and depression have been positively associated with religiosity among Black MSM (Watkins et al 2016).…”
Section: Introductionmentioning
confidence: 99%